Research on artificial intelligence technology and the future intelligent information service architecture - Zhihong WANG; Zhen YANG (Dianxin kexue)
The concept and research of artificial intelligence,cognitive computing,decision support have been taken out of the laboratory and into the real practical stage.Its practical value has exceeded the initial understanding of technical researchers,and its essence is the technology of how to process information and data.It will give people better life and have great effect on the architecture of future society and organization.Firstly,the basic concept of artificial intelligence technology was introduced.And then the artificial intelligence technology for the future economic life of the important significance,artificial intelligence technology development,accumulation,reuse,platform characteristics and the problems they faced were studied.Finally,the operators' research and application strategy of artificial intelligence technology were analyzed.